Incidents associated with delayed bladder catheterization in hospitalized patients: an integrative review (Research, Society and Development, 2020)
This study aimed to discuss the evidence found in the national and international scientific literature, regarding the incidents associated with bladder catheterization of delay in hospitalized patients. This is an integrative review, supported by the PRISMA recommendation. The search took place from October to December 2018, through the following sources of information: PubMed, Cochrane, LILACS, BDENF and CINAHL, applying the filters: full articles, from 2013 to 2019 in English, Spanish and Portuguese and using the descriptors “Urinary catheterization / Urinary catheterization”; "Enfermagem / Nursing"; “Patient safety / Patient safety”; “Near miss / Near Miss, Healthcare”; "Damage to the patient / Patient Harm". The final sample of the study consisted of 20 articles. In data analysis, the articles were classified into 2 units of analysis, namely: main incidents associated with the use of CVD in hospitalized patients and adequacy of the use of CVD as a preventive method for the occurrence of incidents. Catheter-associated Urinary Tract Infection (CAITU) was the most recurrent incident. The study identified that Catheter-associated Urinary Tract Infection (CAITU) was the most recurrent incident and that continuous assessment of the risks associated with CVD contributes to the early identification and mitigation of potential incident occurrences during insertion, maintenance and handling this device. The research proved to be relevant for the advancement and consolidation of the patient safety knowledge field.